The factors influencing the adoption and sustainability of digital technologies by healthcare providers in South Africa - Mhlauli, Luyanda (University of the Witwatersrand, Johannesburg, 2023)
Healthcare has become the most rapidly growing sector in developing and developed countries due to it being a constitutional right and its importance in maintaining the lives of citizens in South Africa. Evidence shows that the quality and access to health care in South Africa face several challenges which date back to the history of the country and the increasing burden of disease. Despite several initiatives and interventions that have been implemented, the state of the healthcare system continues to deteriorate. The effect of rapid technology change has resulted in the emergence of digital health technologies which aim to transform the industry by reducing costs, improving efficiencies, introducing new players in the healthcare value chain and empowering patient and healthcare players with information that enables improved health outcomes. Despite, recognising the benefits of digital health technologies to address the challenges that the sector experience, the successful implementation of these solutions has been limited. The purpose of this study is to understand the factors influencing the intended adoption and sustainability of digital transformation technologies in the South African Healthcare sector. The factors influencing the intended adoption and sustainability of digital technologies are uncovered by understanding the critical factors experienced by various stakeholders in the South African healthcare sector value chain which include the implementation, funding, technology partnerships, technology development, governance, research, healthcare provision, and usage of healthcare services when adopting digital health technologies The findings revealed that several digital health technologies have been implemented across South Africa, however, the focus of technologies has been on the smaller populated private sector. Data also showed that the implementations spanned across the common solutions of mHeatlh, eHealth, and telemedicine and are underpinned by AI, ML, Big Data and predictive analytics. However, the anticipated benefits are not being realised by the greater South Africa to improve health outcomes and improve the access and quality of healthcare
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital Adoption; Digital Sustainability; Factors Influencing Digital Technology Adoption; Digital Transformation; Digital Technologies; Digital Health Technologies; South Africa; Qualitative Research; UCTD; SDG-9: Industry, innovation and infrastructure